2007
DOI: 10.1016/j.biopsych.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Post-Pubertal Disruption of Medial Prefrontal Cortical Dopamine–Glutamate Interactions in a Developmental Animal Model of Schizophrenia

Abstract: Background-A neonatal ventral hippocampal lesion (NVHL) induces behavioral and physiological anomalies mimicking pathophysiological changes of schizophrenia. Because prefrontal cortical (PFC) pyramidal neurons recorded from adult NVHL rats exhibit abnormal responses to activation of the mesocortical dopaminergic (DA) system, we explored whether these changes are due to an altered DA modulation of pyramidal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 42 publications
3
89
0
1
Order By: Relevance
“…Third, TTX-induced reductions in functional activity may result in populations of affected neurons being more susceptible to anomalous pruning during the adolescent-puberty period (Teicher et al, 2003). The well-known manifestation of a SZ-like phenotype at the time of late puberty in these various hippocampal-based models (Alexander et al, 2009;Tseng et al, 2007) of the disorder may relate, in part, to the timing of this inappropriate pruning. Finally, TTX-induced changes in impulse flow may diminish myelination of hippocampal and other projection neurons, during the sensitive period around PD7, but not PD32 (Suzuki and Raisman, 1994;Zalc and Fields, 2000).…”
Section: Age-and Regional-dependent Effects Of Ttx Infusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, TTX-induced reductions in functional activity may result in populations of affected neurons being more susceptible to anomalous pruning during the adolescent-puberty period (Teicher et al, 2003). The well-known manifestation of a SZ-like phenotype at the time of late puberty in these various hippocampal-based models (Alexander et al, 2009;Tseng et al, 2007) of the disorder may relate, in part, to the timing of this inappropriate pruning. Finally, TTX-induced changes in impulse flow may diminish myelination of hippocampal and other projection neurons, during the sensitive period around PD7, but not PD32 (Suzuki and Raisman, 1994;Zalc and Fields, 2000).…”
Section: Age-and Regional-dependent Effects Of Ttx Infusionsmentioning
confidence: 99%
“…Rats sustaining lesions of the VH as neonates exhibit a wide range of neuropathologies believed to contribute to the cognitive symptoms of SZ, including functional deficits in hippocampal (Francois et al, 2009) and prefrontal interneurons (Mitchell et al, 2005;Francois et al, 2009), abnormal dopamine-glutamate regulation of prefrontal and accumbens neuronal excitability (Tseng et al, 2007), reduced dendritic spine density in PFC (Marquis et al, 2008), and dysregulated cortical acetylcholine (ACh) release (Alexander et al, 2009;Laplante et al, 2004). Not surprisingly, animals with such lesions also develop abnormal behaviors during or after adolescence that resemble those seen in SZ, including hypersensitivity to stimulants and NMDA antagonists (Flores et al, 1996;Lipska et al, 2002b), impairments in working memory (Brady et al, 2010;Lipska et al, 2002a), and deficits in cognitive flexibility (Marquis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although the discrepancy in anatomical findings between this model and schizophrenia are great, it prevails to be an attractive model because of its implications in the dopaminergic system, a neurotransmitter system known to be affected in this disorder and a major target for therapeutic agents. Recent investigations using this model examined cell excitability in PFC neurons, and it was concluded that the PFC dopamine-glutamate interactions were altered after puberty in the lesioned rats (Tseng et al, 2007). Specifically, the PFC neurons showed enhanced excitability in lesioned animals, which contradicts the common concept of hypofrontality, characteristic of schizophrenic subjects.…”
Section: Animal Models Involving the Hippocampusmentioning
confidence: 99%
“…(B) Postnatal development of the number of neurons (yellow traces) and nonneuronal cells (blue) for whole rat brain (WB), cerebral cortex (Ctx, with the scale in parentheses), and cerebellum (Cb) (Bandeira et al, 2009;Mortera and Herculano-Houzel, 2012) indicates rapid changes in rodents during the first 3 postnatal weeks, the cell numbers remaining rather stable after that. (C) Timelines for the brain developmental processes important for the functions of neuronal and various glial cells. in different brain regions, with the DAergic and GABAergic systems of the cortex developing late (Tseng et al, 2007;Hashimoto et al, 2009;Kilb, 2012;Manitt et al, 2013;Ouellet and de Villers-Sidani, 2014). Fourth, various neurotrophic factors and their receptors have differential expression profiles in various brain regions (Perovic et al, 2013).…”
Section: E Developmental Maturation Of the Brain In Rodents And Humansmentioning
confidence: 99%